Band-like transport in high vacuum thermal reduced graphene oxide films. (July 2019) - Silipigni, L.; Salvato, G.; Di Marco, G.; Fazio, B.; Torrisi, A.; Cutroneo, M.; Torrisi, L.
Abstract: Measurements of electrical conductivity were carried out at temperatures ranging between 77 K and 450 K on high vacuum thermal reduced graphene oxide (rGO) films. The investigated samples were characterized in composition and structure before being analyzed in terms of electrical conduction. Their electrical conductivity was also measured in air at room temperature. Measurements have demonstrated that at first graphene oxide (GO) was not stable both in air and vacuum. It stabilized after having been subjected to 7 thermal cycles under high vacuum conditions, about 10 −7 torr, up to a Tmax of 450 K. At room temperature the initial GO material had a very low conductivity, of the order of 10 −10  Ω −1 x cm −1, which increased to about 2.5 Ω −1 x cm −1 when it was thermal stabilized in rGO. The stabilization process, induced by the high vacuum heating procedure, seems due to a good reduction of GO, which gives rise to such expansion of the conjugated π-electron system that a band-like transport with small thermal activation energies (Ea  = 10–50 meV) occurs. The performed electrical conductivity measurements are presented and discussed. Highlights: Effects of temperature and high vacuum on the graphene oxide electrical conductivity. A band-like transport with small thermal activation energies occurs in stabilized rGO. High vacuum thermal rGO is a high conductivity semiconductor with good sp 2 character. Band structure scheme for the GO high vacuum assisted thermal reduction is proposed. Simple method to reduce GO and to stabilize rGO by thermal cycles in high vacuum.